Process for preparing super cable core material based on vacuum hot pressing method

The vacuum hot pressing method is used to composite graphene and copper to prepare a super cable core material with excellent electrical conductivity, mechanical strength and thermal conductivity, which solves the problem of high energy consumption, complicated process and limited improvement in electrical conductivity performance of the existing cable core material preparation process. problems and realized the industrial application of high-performance cables.

CN119340028APending Publication Date: 2025-01-21KUNMING UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411729294.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing cable core preparation process has problems such as high energy consumption, complex processes, and limited electrical conductivity improvement, which is difficult to meet the needs of modern power systems for high-performance cables.

Method used

The vacuum hot pressing method is used to composite nanocarbon materials (such as graphene) with metal substrates (such as copper). By optimizing process parameters and material combinations, super cable core materials with excellent electrical conductivity, mechanical strength and thermal conductivity are prepared.

Benefits of technology

The conductivity of the super cable core material is increased by 1-10%, the strength is increased by 10-50%, the thermal conductivity is significantly improved, the production cost is reduced, the process is simplified, and it is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of cable core material preparation, and discloses a process for preparing a super cable core material based on a vacuum hot pressing method. According to the process, graphene and high-purity copper foil are used as raw materials, graphene is dispersed in absolute ethyl alcohol to be subjected to ultrasonic treatment to obtain dispersion liquid, then the dispersion liquid is sprayed to the surface of the copper foil to be stacked, and the super cable core is prepared through the working procedures of vacuum hot pressing, annealing, hot extrusion to form a bar, drawing and the like, the hardness of the cable core material prepared through the process is improved to 80 HV, the tensile strength is improved to 280 MPa, and the tensile strength is improved to 280 MPa. According to the present invention, the electrical conductivity is increased to 104.5% IACS, the thermal conductivity reaches 450 W / m.K, the process is simple, the cost is low, the product consistency is good, the industrial production is easily achieved, the cable performance can be effectively improved, and the requirements of the electric power system are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cable core material preparation, and in particular to a process for preparing super cable core material based on vacuum hot pressing. Specifically, nano carbon materials (such as graphene, carbon nanotubes) are compounded with metal matrices (such as copper, aluminum) by vacuum hot pressing to prepare super cable core material with excellent electrical conductivity, mechanical strength and thermal conductivity, as well as the application of the cable core material in power cables. Background Art

[0002] Current status and demand of cable industry

[0003] With the continuous advancement of science and technology, modern power systems have increasingly higher performance requirements for cables. Traditional cable materials have gradually shown limitations in high current and high voltage transmission and cannot meet the growing demand for electricity. For example, in long-distance power transmission and urban power grid upgrades, cables are required to have higher conductivity, better thermal conductivity and stronger mechanical strength to reduce transmission losses, improve power transmission efficiency and ensure the service life of cables.

[0004] Disadvantages of existing cable core material preparation methods

[0005] Limitations of traditional cable core material preparation technology

[0006] The traditional preparation process of copper core materials includes electrolytic copper smelting, continuous casting, rolling, annealing, drawing and other processes. Although it can meet certain performance requirements, it has problems such as high energy consumption, complex processes and limited improvement in the conductivity of the final product. The best conductivity of traditional copper cables generally only reaches 97% IACS, which is difficult to meet the needs of efficient power transmission.

[0007] The preparation of aluminum core materials also faces similar problems. Multiple process parameters need to be strictly controlled during the preparation process, but there is still much room for improvement in improving conductivity and mechanical strength.

[0008] Problems with the preparation method of new cable core materials

[0009] Application limitations of superconducting cables

[0010] Superconducting cables use the zero resistance characteristics of superconducting materials to achieve low-loss power transmission. my country has also successfully developed and put into operation the first new superconducting cable. However, the application of superconducting cables faces many limitations. The key technology lies in the performance of superconducting materials and the efficiency and cost of the refrigeration system. At present, the preparation process of superconducting materials is complex and costly, and special equipment and environment are required to maintain the superconducting state, such as a low-temperature refrigeration system. Taking the superconducting cables that have been put into operation in my country as an example, their refrigeration system consumes a lot of energy to maintain a low-temperature environment, which not only increases the operating cost, but also puts higher requirements on energy supply. In addition, the manufacturing technology of superconducting cables is difficult, and quality control and stability assurance in the production process are also a challenge. These factors make it difficult for superconducting cables to be widely promoted and applied at present, and they are only piloted in some specific scenarios with extremely high requirements for transmission capacity and loss, such as high-load power supply areas in urban centers or power supply for large scientific research facilities.

[0011] Cable core material issues of graphene grown on structured copper substrate

[0012] Although the patent for the method of growing graphene on a structured copper substrate obtained by Chint Electric provides a new idea for the preparation of cable core materials, there are still some problems in practical applications. In the preparation process, copper powder and copper foil are alternately stacked and placed in a mold, and then graphene is grown by chemical vapor deposition after isostatic pressing. However, this method is difficult to ensure the uniform growth and high-quality bonding of graphene on the copper substrate during large-scale production. During the isostatic pressing process, the problem of inconsistent material density caused by uneven pressure may occur, thereby affecting the bonding effect of graphene and the copper substrate. Moreover, the process parameter control of the chemical vapor deposition method is relatively complex. For example, slight changes in parameters such as gas flow, temperature, and pressure may affect the growth quality and growth rate of graphene, and thus affect the performance stability of the cable core material. In actual production, the precise control of these parameters requires high-precision equipment and strict process management, which increases production costs and production difficulties.

[0013] Problems with graphene-reinforced copper-based composites

[0014] Preparation issues of graphene / copper composite powders

[0015] Electrochemical Deposition Problems

[0016] When preparing graphene / copper composite powders by electrochemical deposition, the selection and composition control of the electrolyte are crucial. Different electrolyte systems will affect the deposition rate and quality of graphene. For example, if the ion concentration in the electrolyte is not appropriate, it may lead to uneven deposition of graphene on the copper substrate, local agglomeration or insufficient deposition. The deposition current density is also a key factor. Too high a current density may cause agglomeration and increased defects in the graphene sheets, while too low a current density will lead to low deposition efficiency. In actual operation, precise control of current density requires high-precision power supply equipment and real-time monitoring systems, which increases the complexity and cost of the process. In addition, side reactions during electrochemical deposition may also affect the properties of the composite material. For example, the precipitation of hydrogen may cause pores to form inside the composite material, reducing its density and mechanical properties.

[0017] Molecular Mixing Problems

[0018] The molecular-level mixing method can theoretically achieve fine mixing of graphene and copper powder, but it faces many difficulties in actual operation. There are strong van der Waals forces between graphene sheets, which are easy to agglomerate to form larger aggregates, making it difficult to achieve uniform dispersion in copper powder. Even if some dispersion measures are taken during the mixing process, such as ultrasonic treatment, graphene may still re-agglomerate during subsequent drying and processing. Moreover, the molecular-level mixing method has high requirements for equipment and operating environment, and needs to be carried out under the protection of inert gas to prevent oxidation of graphene and copper powder, which increases the difficulty and cost of the process. During the sintering process, due to the large difference in the thermal expansion coefficients of graphene and copper powder, thermal stress is easily generated, resulting in cracks and defects inside the composite material, affecting its performance.

[0019] Problems with in situ synthesis

[0020] In the in-situ synthesis method, when polymethyl methacrylate (PMMA) is used as a solid carbon source to in-situ grow graphene on flaky copper powder, the decomposition of the carbon source and the growth process of graphene are difficult to accurately control. The decomposition temperature and rate of PMMA will affect the growth quality and number of layers of graphene. If the decomposition is incomplete, impurities may remain in the composite material, affecting its conductivity and mechanical properties. During the growth process, the interface reaction between graphene and the copper matrix is ​​also more complicated, and some interface phases that are not conducive to performance improvement may be formed. For example, some interface products such as carbides or oxides may be generated, which reduces the bonding strength between graphene and the copper matrix, thereby affecting the overall performance of the composite material. Moreover, the reaction conditions of the in-situ synthesis method are relatively harsh, requiring high temperature, high pressure and other conditions, and have high requirements on equipment, which is not conducive to large-scale production.

[0021] Powder Metallurgy Problems

[0022] When preparing graphene / copper composite materials by powder metallurgy, the high temperature and high pressure treatment process has a destructive effect on the graphene structure. During hot pressing or hot extrusion molding, high temperature may cause some chemical bonds of graphene to break, causing it to lose some of its excellent properties. At the same time, high pressure may cause graphene sheets to stack and twist, affecting their dispersion state and enhancement effect in the copper matrix. In addition, during the preparation process of powder metallurgy, the mixing uniformity of metal powder and graphene powder is difficult to ensure, and it is easy to have a local graphene content that is too high or too low, resulting in uneven performance of the composite material. During the sintering process, there are also problems with the interface diffusion and bonding between graphene and the copper matrix. If the interface bonding is not tight, cracks are easily generated at the interface when subjected to force, reducing the strength and toughness of the composite material.

[0023] Problems in preparing composite foil by directly combining graphene with bulk copper foil

[0024] Electrophoretic Sedimentation Problems

[0025] In the electrophoretic deposition method, the stability and composition of the electrophoretic solution have a significant impact on the deposition effect of graphene on the copper foil surface. The pH value, ionic strength and other factors of the electrophoretic solution need to be precisely controlled, otherwise the graphene is easy to agglomerate and precipitate, and cannot be evenly deposited on the copper foil surface. For example, when the pH value deviates from the appropriate range, the charge state of the graphene surface changes, resulting in an unstable migration rate during the electrophoresis process, and it is easy to form agglomerates. The control of deposition voltage and time is also critical. Inappropriate voltage and time may lead to insufficient or uneven graphene deposition. Moreover, the bonding between graphene and copper foil after electrophoretic deposition mainly relies on physical adsorption, and the bonding force is relatively weak. In subsequent processes such as hot pressing and rolling, graphene is easy to fall off from the surface of the copper foil or delaminate, affecting the performance stability of the composite material. In addition, the production efficiency of the electrophoretic deposition method is low, and it is difficult to meet the needs of large-scale production.

[0026] Chemical Vapor Deposition Problems

[0027] When growing graphene by chemical vapor deposition, precise control of process parameters is a huge challenge. Slight changes in parameters such as gas flow, temperature, and pressure will have a significant impact on the growth quality of graphene. For example, uneven gas flow may lead to inconsistent growth rates of graphene on the surface of copper foil, resulting in uneven thickness. Too high or too low temperature will affect the crystallization quality and growth rate of graphene, and may cause defects or uneven growth of multilayer graphene. Pressure fluctuations will also affect the diffusion and adsorption process of the reaction gas, thereby affecting the growth of graphene. Graphene grown on the surface of copper foil may have defects, such as lattice defects and edge defects, which will affect its bonding with copper foil and its conductive properties. Moreover, chemical vapor deposition requires the use of some toxic and harmful gases, such as methane and hydrogen, which are harmful to the environment and the health of operators and do not meet environmental protection requirements. During hot pressing and rolling, due to the different thermal expansion coefficients of graphene and copper foil, internal stress is easily generated, resulting in deformation and performance degradation of the composite material. In addition, the growth direction and number of graphene layers on the copper foil surface are difficult to control accurately, which poses a challenge to the uniformity and repeatability of the composite material's performance. For example, different batches of graphene may have differences in the number of layers and orientation, which makes the performance of the composite material fluctuate greatly, making it difficult to ensure the stability of product quality.

[0028] The need for research

[0029] Therefore, developing a new cable core material preparation process can effectively solve existing problems and improve the comprehensive performance of cable core materials, which is of great significance for promoting technological progress in the cable industry and meeting the development needs of power systems. The present invention aims to prepare nano-carbon reinforced metal matrix composite materials by vacuum hot pressing, overcome the shortcomings of the existing technology, and achieve comprehensive improvement of cable core material performance. Summary of the invention

[0030] Purpose of the Invention

[0031] The purpose of the present invention is to provide a process for preparing super cable core materials based on vacuum hot pressing. By optimizing process parameters and material combinations, the prepared cable core materials have excellent electrical conductivity, mechanical strength and thermal conductivity to meet the high performance requirements of modern power systems for cables, while reducing production costs and realizing industrial applications.

[0032] Technical Solution

[0033] A process for preparing a super cable core material based on a vacuum hot pressing method, characterized in that the super cable core material is prepared from the following raw materials in parts by weight:

[0034] 3~5 parts of graphene and 90~110 parts of high-purity copper foil.

[0035] According to claim 1, the purity of the high-purity copper foil is 99.999%, and the thickness of the copper foil is 0.05-0.2 mm.

[0036] The method for preparing the super cable core material according to any one of claims 1, characterized in that it comprises the following steps:

[0037] Dispersing graphene in anhydrous ethanol to form a graphene suspension;

[0038] The solution obtained by preliminary mixing in step (1) is placed in an ultrasonic disperser for ultrasonic treatment to obtain a graphene dispersion;

[0039] Spraying the graphene dispersion of step (2) onto the surface of the high-purity copper foil in a layer-by-layer manner;

[0040] Placing the graphene / copper composite foil stacked in step (3) in a vacuum hot press for hot pressing;

[0041] Annealing the composite material obtained by hot pressing in step (4) in a high temperature box furnace;

[0042] Hot extruding the composite material obtained by annealing in step (5) into a rod;

[0043] The rod obtained in step (6) is subjected to a drawing process to obtain a super cable core.

[0044] Preferably, the concentration of the graphene suspension prepared in step (1) is 1-5 mg / mL.

[0045] Preferably, the ultrasonic frequency used in step (2) is 30-40 kHz, the ultrasonic power is 200-400 W, and the ultrasonic time is 90-120 min.

[0046] Preferably, the number of stacked layers of graphene / copper composite foil obtained in step (3) is 20 to 100.

[0047] Preferably, the hot pressing temperature in step (4) is 300° C. to 600° C., and the hot pressing time is 1 to 4 hours.

[0048] Preferably, the annealing temperature in step (5) is 200° C. to 500° C., and the annealing time is 1 to 2 h.

[0049] Preferably, the diameter of the rod obtained by hot extrusion in step (6) is 8 to 10 mm.

[0050] Preferably, the cross-sectional area of ​​the super cable core obtained by drawing in step (7) is 1.5-10 mm 2 .

[0051] Beneficial Effects

[0052] Performance Improvements

[0053] The conductivity of the super cable core material prepared by the process of the present invention can be increased by 1-10% on the basis of the substrate, which is greatly improved compared with similar graphene copper composite metals, and the strength can be increased by 10-50% on the basis of the substrate. For example, taking the copper core material as an example, the improvement of conductivity helps to reduce the annual power loss of the national power grid, which is equivalent to reducing a large amount of carbon dioxide emissions, and is of great significance for energy conservation and environmental protection.

[0054] The thermal conductivity of the composite material has also been significantly improved, which can better dissipate heat, ensure the stability of the cable during high current transmission, and extend the service life of the cable.

[0055] Cost reduction and industrial feasibility

[0056] The process of the present invention is relatively simple, easy to operate and control, and can effectively reduce production costs. Compared with the traditional cable core material preparation process, it reduces complex processes and waste of raw materials and improves production efficiency.

[0057] By optimizing process parameters and material combinations, the consistency and stability of products are improved, which is conducive to large-scale industrial production and meets the market demand for high-performance cable core materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 This is a tensile fracture diagram of the graphene / copper composite material prepared by hot pressing in Example 1 of the present invention

[0059] Figure 2 This is a tensile fracture diagram of the graphene / copper composite material prepared by hot pressing in Example 2 of the present invention

[0060] Figure 3 This is a tensile fracture diagram of the graphene / copper composite material prepared by hot pressing in Example 3 of the present invention DETAILED DESCRIPTION

[0061] The present invention will be further described below in conjunction with specific examples. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0062] Example 1

[0063] Raw material preparation

[0064] Prepare the raw materials according to the following weight parts: 3 parts of graphene and 90 parts of high-purity copper foil, wherein the purity of the high-purity copper foil is 99.99% and the thickness is 0.05 mm.

[0065] Preparation of graphene suspension

[0066] Graphene was dispersed in anhydrous ethanol and ultrasonically treated using an ultrasonic disperser. The ultrasonic frequency was set to 30 kHz, the ultrasonic power was 200 W, and the ultrasonic time was 90 min to obtain a suspension with a concentration of 1 mg / mL.

[0067] Stacking and hot pressing

[0068] The graphene dispersion was sprayed on the surface of high-purity copper foil, and 20 layers were stacked one by one. Then, the resulting composite material was placed in a vacuum hot press and hot-pressed at 300°C for 1 hour.

[0069] Annealing

[0070] The hot-pressed material was placed in a high-temperature box furnace and annealed at 200°C for 1 h.

[0071] Hot extrusion and drawing

[0072] The annealed material is hot extruded into a rod with a diameter of 8mm, and then the rod is drawn to produce a super cable core with a cross-sectional area of ​​1.5mm². The hardness of the cable core is finally increased to 100HV, the tensile strength is increased to 330MPa, the conductivity is further increased to 100.5%IACS, and the thermal conductivity reaches 380W / m·K.

[0073] Example 2

[0074] Raw material preparation

[0075] Prepare the raw materials according to the following weight parts: 3 parts of graphene and 90 parts of high-purity copper foil, wherein the purity of the high-purity copper foil is 99.99% and the thickness is 0.05 mm.

[0076] Preparation of graphene suspension

[0077] Graphene was dispersed in anhydrous ethanol and ultrasonically treated using an ultrasonic disperser. The ultrasonic frequency was set to 30 kHz, the ultrasonic power was 200 W, and the ultrasonic time was 90 min to obtain a suspension with a concentration of 1 mg / mL.

[0078] Stacking and hot pressing

[0079] The graphene dispersion was sprayed on the surface of high-purity copper foil, and 20 layers were stacked one by one. Then, the resulting composite material was placed in a vacuum hot press and hot pressed at 400°C for 1.5 hours.

[0080] Annealing

[0081] The hot-pressed material was placed in a high-temperature box furnace and annealed at 200°C for 1 h.

[0082] Hot extrusion and drawing

[0083] The annealed material is hot extruded into a rod with a diameter of 8mm, and then the rod is drawn to produce a super cable core with a cross-sectional area of ​​1.5mm². The hardness of the cable core is finally increased to 92HV, the tensile strength is increased to 300MPa, the conductivity is further increased to 102%IACS, and the thermal conductivity reaches 410W / m·K

[0084] Example 3

[0085] Raw material preparation

[0086] The raw materials were prepared according to the following weight proportions: 3 parts of graphene and 90 parts of high-purity copper foil, wherein the purity of the high-purity copper foil was 99.99% and the thickness was 50 μm.

[0087] Preparation of graphene suspension

[0088] Graphene was dispersed in anhydrous ethanol and ultrasonically treated using an ultrasonic disperser. The ultrasonic frequency was set to 30 kHz, the ultrasonic power was 200 W, and the ultrasonic time was 90 min to obtain a suspension with a concentration of 1 mg / mL.

[0089] Stacking and hot pressing

[0090] The graphene dispersion was sprayed on the surface of high-purity copper foil, and 20 layers were stacked one by one. Then, the resulting composite material was placed in a vacuum hot press and hot pressed at 500°C for 2 hours.

[0091] Annealing

[0092] The hot-pressed material was placed in a high-temperature box furnace and annealed at 200°C for 1 h.

[0093] Hot extrusion and drawing

[0094] The annealed material is hot extruded into a rod with a diameter of 8mm, and then the rod is drawn to produce a super cable core with a cross-sectional area of ​​1.5mm². The hardness of the cable core is finally increased to 80HV, the tensile strength is increased to 280MPa, the conductivity is further increased to 104.5%IACS, and the thermal conductivity reaches 450W / m·K.

Claims

1. A process for preparing super cable core material based on vacuum hot pressing method, characterized in that: The super cable core material is prepared from the following raw materials in parts by weight: 3~5 parts of graphene and 90~110 parts of high-purity copper foil.

2. According to claim 1, the purity of the high-purity copper foil is 99.999%, and the thickness of the copper foil is 0.05-0.2 mm.

3. The method for preparing the super cable core material according to any one of claims 1, characterized in that: The following steps are involved: (1) dispersing graphene in anhydrous ethanol to form a graphene suspension; (2) placing the solution preliminarily mixed in step (1) in an ultrasonic disperser for ultrasonic treatment to obtain a graphene dispersion; (3) spraying the graphene dispersion of step (2) onto the surface of the high-purity copper foil and stacking them layer by layer; (4) placing the graphene / copper composite foil stacked in step (3) in a vacuum hot press for hot pressing; (5) annealing the composite material obtained by hot pressing in step (4) in a high temperature box furnace; (6) hot extruding the composite material obtained by annealing in step (5) into a rod; (7) The rod obtained in step (6) is subjected to a drawing process to obtain a super cable core.

4. The method for preparing a super cable core material according to claim 3, characterized in that: The concentration of the graphene suspension prepared in step (1) is 1-5 mg / mL.

5. The method for preparing the super cable core material according to claim 3, characterized in that: The ultrasonic frequency used in step (2) is 30-40 kHz, the ultrasonic power is 200-400 W, and the ultrasonic time is 90-120 min.

6. The method for preparing a super cable core material according to claim 3, characterized in that: The number of stacked layers of the graphene / copper composite foil obtained in step (3) is 20 to 100.

7. The method for preparing a super cable core material according to claim 3, characterized in that: The hot pressing temperature in step (4) is 300°C to 600°C, and the hot pressing time is 1 to 4 hours.

8. The method for preparing a super cable core material according to claim 3, characterized in that: The annealing temperature in step (5) is 200°C to 500°C, and the annealing time is 1 to 2 hours.

9. The method for preparing a super cable core material according to claim 3, characterized in that: The diameter of the rod obtained by hot extrusion in step (6) is 8-10 mm.

10. The method for preparing a super cable core material according to claim 3, characterized in that: The cross-sectional area of ​​the super cable core obtained by drawing in step (7) is 1.5~10mm 2 .